Challenges Facing Information Systems Security Management in Higher Learning Institutions: A Case Study of the Catholic University of Eastern Africa - Kenya - Okibo, Bichanga Walter; Ochiche, Obara Brigit (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
With the popularity of internet applications, many organizations are facing unprecedented security challenges. Security techniques and management tools have caught a lot of attention from both academia and practitioners. However, there is lacking a theoretical framework for the challenges facing information security management in higher learning institutions. Thus this research looked into the challenges facing information systems security management in higher learning institutions. The study was guided by understanding the major challenges facing Information Systems Security Management and establishing the extent of the use of Information Systems Security Management in higher learning institutions. The study used descriptive survey design. It targeted information systems projects managers, administrators or top management and other users (staff) of the systems in key departments. Systematic sampling strategy was used. Descriptive statistics of SPSS were used to analyze the data. Factor analysis technique was used to identify the major challenges that affect management of an institution’s information system security. Pearson’s Chi-Square was used to test the relationships that exist between the categorical variables. The study found out that system vulnerability, computer crime and abuse, environmental security and financial backing/security are key challenges institutions of higher learning are experiencing in the management of their information systems. The study recommends the implementation of new policies and procedures to guide information system security. Programs for monitoring and evaluating information systems security in relation to performance indicators should be put in place. Institutions should invest heavily in developing their staff through training programmes such as seminars, workshops and conferences to further develop staff skills and abilities on information systems security issues.